Recovery of Sn, Ag and Cu from waste Pb-free solder using nitric acid leaching - Yoo, Kyoungkeun; Lee, J.; Lee, K.; Kim, B.; Kim, M.; Kim, S.; Pandey, B. (Japan Institute of Metals and Materials, 2012)
The development of a hydrometallurgical process for the recycling of waste Pb-free solder based on nitric acid leaching, followed by the separation of Ag and Cu through AgCl precipitation or cementation, was investigated. Nitric acid dissolved Cu and Ag from the waste material while converting tin to stannic oxide (SnO2), which is very sparingly soluble in the HNO3 solution. More than 99% of the Ag and Cu in the waste Pb-free solder were dissolved in 2 kmol·m-3 HNO3 under the leaching conditions of 75°C, 100 kg·m-3 pulp density and stirring at 400 rpm for 120 min. The addition of NaCl or Cu powder was used to separate Ag from Cu in the solution. The addition of 2 kg·m-3 of NaCl or 125 kg·m-3 of Cu powder to the leaching solution at 30°C led to the successful recovery of 3755 g·m-3 of Ag. Thus, the results showed that Sn, Ag and Cu could be separated and recovered from waste Pb-free solder by the proposed recycling process. © 2012 The Japan Institute of Metals.